Hyperglycemia and Phosphatidylinositol 3‐Kinase/Protein Kinase B/Mammalian Target of Rapamycin (PI3K/AKT/mTOR) Inhibitors in Phase I Trials: Incidence, Predictive Factors, and Management. (5th May 2016) - Khan, Khurum H.; Wong, Mabel; Rihawi, Karim; Bodla, Shankar; Morganstein, Daniel; Banerji, Udai; Molife, Lulama R.
Abstract : Background: Dysregulation of the phosphatidylinositol 3‐kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway is implicated in human cancer growth and progression. Agents targeting this pathway are associated with hyperglycemia due to interaction with the insulin‐glucose regulatory axis. Identifying the predictive factors for hyperglycemia in patients treated with these agents may help direct future management. Materials and Methods: Clinical characteristics and outcomes of patients treated consecutively with PI3K, AKT, or mTOR inhibitors in the Drug Development Unit, The Royal Marsden (RM) National Health Service (NHS) Foundation Trust, between 2007 and 2012 were recorded. Baseline variables and their association with grade 3 hyperglycemia (Common Terminology Criteria for Adverse Events, version 3.0) were analyzed by using the chi‐square test and Fisher exact test for categorical variables and binary logistic regression for continuous variables. Results: A total of 341 patients were treated in 12 phase I trials of PI3K/AKT/mTOR inhibitors, and 298 patients (87.4%) developed hyperglycemia. Hyperglycemia was grade 1 in 217 (72.8%) and grade 2 in 61 (20.5%) patients, respectively. Grade ≥3 hyperglycemia was seen in 6.7% of patients ( n = 20). According to the chi‐square test, age <65 years ( p = .03), history of diabetes ( p = .003), and treatment with AKT and dual PI3K/mTOR inhibitors ( p < .0005) predicted the occurrence of grade 3 hyperglycemia. Of 24 patients requiring intervention, 20 received metformin, 2 dietary advice, 1 insulin, and 1 both metformin and insulin. One patient required dose reduction. There were no permanent drug discontinuations, and no hyperglycemia‐related dose‐limiting toxicities were observed; thus, the recommended phase II dose was not affected by the hyperglycemia observed in our cohort. Conclusion: Hyperglycemia is common in patients treated with PI3K/AKT/mTOR inhibitors; however, it is manageable with conventional treatment. Predictive factors of age, history of diabetes, and administration of AKT and dual PI3K/mTOR inhibitors warrant prospective validation. Implications for Practice: This study reviewed the clinical data of 341 patients treated in 12 phase I trials of agents targeting phosphatidylinositol3‐kinase (PI3), protein kinase B (AKT), and mammalian target of rapamycin (mTOR), as well as dual inhibitors. Hyperglycemia was evident in 87.4% of patients but was ≥grade 3 in just 6.7%. Age <65 years, history of diabetes, and treatment with AKT and dual PI3K/mTOR inhibitors were each associated with grade 3 hyperglycemia. Management of patients was uncomplicated, and no permanent drug discontinuations were necessary. Despite the small study size, these findings support continued caution about enrolling patients with a history of diabetes into such trials. However, clinicians may be reassured, pending prospective validation of these results, that significant hyperglycemia is not frequent and, when it occurs, is manageable. Abstract : Hyperglycemia is common in patients treated with PI3K/AKT/mTOR inhibitors; however, it is manageable with conventional treatment. Predictive factors of age, history of diabetes, and administration of AKT and dual PI3K/mTOR inhibitors warrant prospective validation.